Kajian Alternatif Penyediaan Avtur (Aviation Turbine) Selain PT.Pertamina (Persero) Bagi Perusahaan Penerbangan di Bandara Soekarno-Hatta - Arman Mardoko (WARTA ARDHIA, 2010)
In supporting fixed the operating of airplane fuel required ready of aviation fuel (aviation turbine) in the airport. During the time ready service of aviation fuel (aviation turbine) in the airport all Indonesia by PT. Pertamina (Persero), with the opening of the door of the liberalization of the which the echo everywhere do Also automatically push the climate emulation of effort this country more and more heat, do not side from levying of fuel in sectors of aviation fuel (aviation turbine). With the cover of ready monopolies of aviation fuel (aviation turbine) in airports by PT. Perlamina (Persero) in the year 2008, hence opening the opportunity for good private sector of national and foreign circles to follow to provide aviation fuel (aviation turbine) in the airport. of research result indicate that the amaunt companies of bunkering aviation fuel (aviation turbine) in ideal airport yetly may not simply, but better to each his every terminal there we one company of bunkering of an airplane, his purpose to lessen vehicle movement of Ground Support Equipment (GSE) and for the shake of safety creation and ordeliness in ramp. All the airlines in principle very is in agreement with opened by the X it and give of opportunity to company besides PT. Pertamina (Persero) to do the bunkering of aviation fuel (aviation turbine) in Soekarno-Hatta Airport.